2011
DOI: 10.2139/ssrn.1915464
|View full text |Cite
|
Sign up to set email alerts
|

Enforcement of Contribution Norms in Public Good Games with Heterogeneous Populations

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 83 publications
2
27
0
Order By: Relevance
“…This also makes the equilibria, and the (interior) social-optimum, more challenging to identify, so the levels of free riding and cooperation are less transparent. Consequently, enforcing social norms of cooperation through peer punishment may become more demanding (Reuben and Riedl, 2013). 5 This CPR environment also creates a more challenging setting for cooperation since the payoff gains to deviating from a cooperative allocation are greater, and the ability of a subgroup of agents to gain from mutual cooperation are weaker, compared to the VCM environment.…”
Section: Public Good Dilemmas In Nonlinear Environmentsmentioning
confidence: 99%
“…This also makes the equilibria, and the (interior) social-optimum, more challenging to identify, so the levels of free riding and cooperation are less transparent. Consequently, enforcing social norms of cooperation through peer punishment may become more demanding (Reuben and Riedl, 2013). 5 This CPR environment also creates a more challenging setting for cooperation since the payoff gains to deviating from a cooperative allocation are greater, and the ability of a subgroup of agents to gain from mutual cooperation are weaker, compared to the VCM environment.…”
Section: Public Good Dilemmas In Nonlinear Environmentsmentioning
confidence: 99%
“…Consensus and compliance may thus differ. While observed behavior remains a crucial measure of compliance with elicited norms, recent experimental work has introduced the explicit use of questionnaires to assess normative consensus (Bicchieri & Chavez, 2010;Bicchieri, Xiao, & Muldoon, 2011;Krupka & Weber, 2013;Rauhut &Winter, 2010;Reuben & Riedl, 2013). In this paper, we therefore measure both the beliefs and behavior of third parties who tradeoff sanctioning, compensating, and rewarding in response to the violation of or compliance with a social norm.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the amount invested in the public good may be chosen from a continuous range of possibilities, depending on individual abilities. Empirical research has shown that human subjects readily accept individual differences and adjust their expectations, punishing only when they believe their co-players invested less than their fair share [28,29]. In our models, we have shown that a sense of "fairness" does seem to emerge in the spatial model, in the sense that punishment is carried out by individuals that are best suited for the task.…”
Section: Future Researchmentioning
confidence: 69%
“…By allowing the costs and benefits of cooperation to vary across sub-classes, individuals from different classes may have different opportunities. Empirical research shows that differences in marginal benefit from contributions to a public good changes the willingness to contribute and punish [28,29]. Subjects that enjoy a higher benefit not only tend to contribute more to the public good, but are also expected to do so, and are punished more severely by other players if they contribute less than their fair share.…”
Section: Introductionmentioning
confidence: 99%